Efektivitas Model Teaching Games for Understanding (TGfU) Terhadap Motivasi Belajar PJOK pada Materi Lari Jarak Pendek Siswa Kelas V Sekolah Dasar - Joko Priyono; Rizki Kurniati; Dewi Ayu Lestari; Ignasius Ivan Kurnia Ndruru; Bangkit Seandi Taroreh (Indonesian Journal of Sport and Tourism, 2026)
This study aimed to analyze the effectiveness of the Teaching Games for Understanding (TGfU) learning model on students’ physical education learning motivation in short-distance running material for fifth-grade elementary school students. The study employed a quantitative approach with a quasi-experimental method using a one-group pretest-posttest design. The research subjects consisted of 21 fifth-grade students at UPT SD Negeri 16 Sei Balai. The sampling technique used was saturated sampling. The research instrument was a physical education learning motivation questionnaire consisting of 35 statements using a Likert scale. Data analysis was conducted using SPSS Statistics 27 through the Shapiro-Wilk normality test, Levene's homogeneity test, and paired sample t-test. The results showed that the average score of students’ physical education learning motivation increased from 102.38 in the pretest to 128.00 in the posttest. The result of the paired sample t-test showed a significance value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest after the implementation of the TGfU learning model. Based on these findings, it can be concluded that the Teaching Games for Understanding (TGfU) learning model is effective in improving students’ physical education learning motivation in short-distance running material at the elementary school level.